Effects of climate and land use changes on water balance in upstream in the Chao Phraya River basin, Thailand - Ponpang-Nga, Pancheewan; Techamahasaranont, Jessada (Agriculture and Natural Resources, 2016)
A monthly water balance model was used to investigate the effects of climatic and land use changes on water resources upstream in the Chao Phraya River basin. The objective was to simulate and predict the hydrological processes under different climate change and land use change scenarios. The results showed that the climatic conditions and land development had an impact on changing the rainfall, evapotranspiration and streamflow. The simulated water balance for future climatic conditions and land use change scenarios showed increases during 2010-2099 in rainfall, temperature, evapotranspiration and streamflow. Under all land use conditions, the estimated evapotranspiration trends increased, especially for the worst case (12% forest area) which showed the highest evapotranspiration values in the A2 and B2 climate change scenarios. When discharge was calculated in the future, there was 27-40% of both A2 and B2 climate change scenarios under all land use conditions (12%, 20% and 40% forest area) when compared between 1970 and 1989 (calibration period) and 2090-2099 (prediction period). Increasing streamflow will be useful for human activities but it raises water resources issues such as the frequency of flood and drought events in the future.